The Effect of Gracilaria verrucosa Seaweed Flour Proportion with White Glutinous Rice Flour (Oryza sativa Glutinosa) and CMC (Carboxy Methyl Cellulose) Concentration on Physical and Chemical Characteristics of Seaweed Dodol - Dieo Riezma Elfahira; Lukman Hudi; Syarifa Ramadhani Nurbaya (Procedia of Engineering and Life Science, 2022)
Gracillaria verrucosa seaweed is one type of agar-producing red algae (agarophyte) that has the potential to be developed because it can be cultivated in polyculture in ponds together with shrimp and crab rearing. Gracillaria verrucosa seaweed is usually used as a raw material for making gelatin, but it would be better to develop it in its processing so that it can produce products that have better economic value and nutritional value by utilizing Gracillaria verrucosa seaweed, and one of these preparations is dodol. This study used factorial RAK (Randomized Block Design) which was repeated 3 times, with the first factor being the proportion of Gracilaria verrucosa seaweed flour with white glutinous rice flour (P) 75%: 25%, 50%: 50%, and 25%: 75%. The second factor is the concentration of CMC (K) 2%, 4%, and 6%. The data were analyzed using analysis of variance and then continued with the BNJ test (Honest Significant Difference) at 5% level. The best treatment was obtained in the P3K3 treatment (the proportion of Gracilaria verrucosa seaweed flour with white glutinous rice flour 75%: 25% and CMC concentration 6%) with color profile L (lightness) 43.1; color profile *a (redness) 4.9; color profile *b (yellowness) 10.6; 1.66N texture water content 37.40%; free fatty acid content of 0.28%; reducing sugar content 0.4%; antioxidant activity 368.6 g/ml.